Agreement between self-reported and objective measures of sleep in people with HIV and lifestyle-similar HIV-negative individuals. (1st June 2021) - De Francesco, Davide; Sabin, Caroline A.; Winston, Alan; Mallon, Patrick W.G.; Anderson, Jane; Boffito, Marta; Doyle, Nicki D.; Haddow, Lewis; Post, Frank A.; Vera, Jaime H.; Sachikonye, Memory; Redline, Susan; et al.
Abstract : Objectives: The aim of this study was to evaluate the agreement between self-reported sleep measures and insomnia with objectively measured sleep parameters in people with HIV (PWH) and HIV-negative individuals. Design: A cross-sectional analysis of PWH and lifestyle-similar HIV-negative individuals. Methods: Self-reported measures included time spent in bed, sleep onset latency and a validated insomnia questionnaire. Objective measures were assessed via 7-days/nights of actigraphy data to determine average and intra-individual variability of several sleep measures (including time spent in bed and onset latency). Spearman's correlation coefficient and Cohen's κ were used to assess the agreement between self-reported and actigraphy-assessed measures. Associations between insomnia and actigraphy-assessed sleep parameters were evaluated using partial least-square discriminant analysis (PLS-DA). Results: We found fair correlation between self-reported and actigraphy-assessed time spent in bed in 342 PWH ( r s  = 0.46) and 119 HIV-negative individuals ( r s  = 0.48). Among PWH, the correlation did not differ by age, education, depressive symptoms and self-reported insomnia (all P  > 0.05), but was stronger in men ( P  = 0.05) and in those with a BMI of at least 25 kg/m 2 ( P  < 0.001). Agreement between self-reported and actigraphy-assessed sleep onset latency was poor in both PWH (κ = 0.002, P  = 0.49) and HIV-negative individuals (κ = 0.009, P  = 0.65). According to PLS-DA, self-reported insomnia most strongly correlated with intra-individual variability of sleep duration, movement index and efficiency. Conclusion: We report poor-to-fair agreement between self-reported and actigraphy-assessed sleep measures in PWH. Insomnia symptoms correlated with regularity of sleep duration, quality and efficiency. These findings highlight the importance of both patient-reported and objective measures of daily sleep variation, for better understanding sleep disorders in PWH. Abstract : Supplemental Digital Content is available in the text